Selection of Influencing Factors on Reverse Logistics Management in Process Industries - S., Robin Divahar; M., Karthikeyan L (Journal of Electronics and Informatics, 2025)
This research investigates concerns on information and logistics management related by means of reverse logistics in the Indian Manufacturing Industries. The study analyzed the factors that influence reverse logistics in that domain. Concerns, including Value Recovery Operations, Return Policy, Reverse Logistics Service, Product Return Operations, Techniques, and Information Technology Enabling Services were tackled to set up reverse logistics’ value in the industries. This study investigated Indian industries which includes process industries through questionnaire survey. The data collected from the survey was analyzed using regression analysis and Friedman Test to understand reverse logistics issues in the firms. Based on the literature and outcomes of the preliminary study, hypotheses were formulated to test their validity while establishing reverse logistics issues in Indian Process industries.